(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Skidan S. O. Motivation of students studying economic profile in the process of learning foreign languages: psychological and pedagogical aspect. The article revealed the structure of learning motivation of students in the process of economic profile ce learning foreign languages. The regularities of formation of learning motivation.